2003
DOI: 10.1161/01.res.0000094746.24774.dc
|View full text |Cite
|
Sign up to set email alerts
|

Mice With a Null Mutation in the NHE1 Na + -H + Exchanger Are Resistant to Cardiac Ischemia-Reperfusion Injury

Abstract: Abstract-Pharmacological studies indicate that Naϩ -H ϩ exchanger isoform 1 (NHE1) plays a central role in myocardial ischemia-reperfusion injury; however, confirmation by alternative methods is lacking. To address this issue, we examined the role of NHE1 in ischemia-reperfusion injury using gene-targeted NHE1-null mutant (Nhe1 Ϫ/Ϫ ) mice. Nhe1Ϫ/Ϫ and wild-type hearts were perfused in a Langendorff apparatus in both the absence and presence of the NHE1 inhibitor eniporide, subjected to 40 minutes of ischemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 48 publications
5
80
1
1
Order By: Relevance
“…An effect of NHE1 to control NHE3 or other transporters also may be relevant to pathophysiological conditions in which NHE1 expression and activity are altered. For example, increased NHE1 activity contributes to ischemic-reperfusion injury of myocardial cells, a process that involves regulatory interactions of NHE1 with other transporters such as Na ϩ / Ca 2ϩ exchange (50,51). Also, NHE1 activity is increased in a variety of cells and tissues in patients with essential hypertension and in hypertensive animal models (52,53), and transgenic mice overexpressing NHE1 exhibit salt-sensitive hypertension in association with renal Na ϩ retention (54).…”
Section: Discussionmentioning
confidence: 99%
“…An effect of NHE1 to control NHE3 or other transporters also may be relevant to pathophysiological conditions in which NHE1 expression and activity are altered. For example, increased NHE1 activity contributes to ischemic-reperfusion injury of myocardial cells, a process that involves regulatory interactions of NHE1 with other transporters such as Na ϩ / Ca 2ϩ exchange (50,51). Also, NHE1 activity is increased in a variety of cells and tissues in patients with essential hypertension and in hypertensive animal models (52,53), and transgenic mice overexpressing NHE1 exhibit salt-sensitive hypertension in association with renal Na ϩ retention (54).…”
Section: Discussionmentioning
confidence: 99%
“…Langendorff Heart Studies-Susceptibility of wild-type and AE3 null hearts (n ϭ 6 hearts/genotype) to impaired cardiac function resulting from I/R injury was analyzed using a Langendorff apparatus as described for the Na ϩ /H ϩ exchanger 1 knock-out (25), except that a 30-min period of no-flow ischemia was used.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of AE3 Did Not Affect Ischemia-Reperfusion InjuryLoss of Na ϩ /H ϩ exchange or Na ϩ /HCO 3 Ϫ cotransport activity protects against I/R injury (19,25,34,35) by reducing the Na ϩ loading that leads to excess Ca 2ϩ loading. Because Cl Ϫ /HCO 3 Ϫ exchange can operate in concert with these acid extrusion mechanisms, thereby enhancing their activities, and has an opposite effect on pH i when operating alone, we analyzed the effect of the AE3 null mutation on I/R injury ( Ϫ/Ϫ and wild-type hearts, respectively) did not differ significantly between the two genotypes (n ϭ 6 for each genotype).…”
Section: Ae3mentioning
confidence: 99%
“…Hoeven et al [12] found progressive organ; particularly kidney dysfunction and inflammatory responses most pronounced in hemodynamically unstable brain-dead donors studied by monitoring LDH levels in Wistar rats. Wang et al evaluated [13] the released LDH levels significantly less impaired in gene-targeted NHE1-null mutant (Nhe1-/-) mice IR hearts relative to wild-type ones, in absence of NHE1 inhibitor. Wang et al [14] measured decreased release of skeletal muscle intracellular enzyme LDH in experimental groups protected by ischemic preconditioning (IP) in limb IR injury compared with the control ones.…”
Section: Discussionmentioning
confidence: 99%